The Contexts of Diaspora Citizenship Somali Communities in Finland and the United States - Armila, Päivi; Kananen, Marko; Kontkanen, Yasemin (International Perspectives on Migration, 2019)
This book explores the social participation, identification and transnational practices of Somalis living in Finland and the United States. Through a multifaceted collection of chapters which are based on data ranging from legislation and policy documents to welfare indicators and interviews, this book explores how Somali migrants experience and explore their identities and belongings, and how they strive for participation as (diaspora) citizens of their sending and receiving societies. The case studies are conducted in two countries that differ greatly in terms of their social system, migration history and integration policies and as such they provide an opportunity to explore how different social, political and legal orders influence the life-courses and wellbeing of migrant populations. Furthermore, the book highlights how the fate of the Somalis as a global diaspora is routinely intertwined with the changes in the global political climate and the state-level political processes reflecting it. This book will be of great interest to researchers, students and lecturers of migration and diaspora, as well as individuals working with (Somali) migrants.